Location of the sources of vibroacoustic disturbances in continuous mechanical objects in the case of a bottling line - ANDRZEJEWSKI, M.; CEMPEL, C. (Archives of Acoustics, 1980)
This paper presents methods of locating sources of vibroacoustic disturances in continuous mechanical objects. This problem is discussed in the case of the bottling line in a food industry enterprise. As a result of the investigations, the methods of investigation presented were found to be valuable. Their application in minimizing the acoustic activity of individual partial sources is also indicated.